THE PROGRESS OF V. VERNADSKY IDEAS IN GEOLOGY - Paranko, I.; Pavlun, M.; Sivoronov, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Human activity has a significant impact on the geological processes. That is why it is proposed to establish the new section in the geological sciences, it is named anthropogenic geology. The purpose – to study the properties, structure, composition and consistent patterns of development of the geological environment which is natural and anthropogenic systems. Overall, this will make it possible to optimally organize resource base of the world and substantiate the correct use of mineral resources.